THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, PROFITABILITY, AND AUDIT QUALITY ON TAX AVOIDANCE IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Limantoro, Prisca Arum; Ardini, Lilis (Jurnal Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), leverage, profitability, and audit quality on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Tax avoidance is measured using the Effective Tax Rate (ETR), CSR is measured using the Corporate Social Responsibility Index (CSRI) based on the Global Reporting Initiative (GRI) G4 guidelines, leverage is proxied by the Debt to Asset Ratio (DAR), profitability by Return on Assets (ROA), and audit quality is measured using a dummy variable distinguishing between Big Four and non-Big Four public accounting firms. This study employs a quantitative approach using secondary data in the form of companies’ financial statements and sustainability reports. The data are analyzed using multiple linear regression with the assistance of SPSS software. The results show that CSR and leverage have a positive effect on tax avoidance, while profitability has a negative effect on tax avoidance, and audit quality has no effect on tax avoidance. Accordingly, CSR activities and debt utilization may be used as tax efficiency strategies, whereas companies with higher profitability tend to be more compliant with tax regulations. The insignificance of audit quality suggests that differences in audit firm size do not determine firms’ propensity to engage in tax avoidance, as auditors are bound by the same auditing standard.